Interplant Aboveground Signaling Prompts Upregulation of Auxin Promoter and Malate Transporter as Part of Defensive Response in the Neighboring Plants - Sweeney, Connor; Lakshmanan, Venkatachalam; Bais, Harsh P. (Frontiers in Plant Science, 2017)
When disrupted by stimuli such as herbivory, pathogenic infection, or mechanical wounding, plants secrete signals such as root exudates and volatile organic compounds (VOCs). The emission of VOCs induces a response in the neighboring plant communities and can improve plant fitness by alerting nearby plants of an impending threat and prompting them to alter their physiology for defensive purposes. In this study, we investigated the role of plant-derived signals, released as a result of mechanical wounding, that may play a role in intraspecific communication between Arabidopsis thaliana communities. Plant-derived signals released by the wounded plant resulted in more elaborate root development in the neighboring, unwounded plants. Such plant-derived signals also upregulated the Aluminum-activated malate transporter (ALMT1) responsible for the secretion of malic acid (MA) and the DR5 promoter, an auxin responsive promoter concentrated in root apex of the neighboring plants. We speculate that plant-derived signal-induced upregulation of root-specific ALMT1 in the undamaged neighboring plants sharing the environment with stressed plants may associate more with the benign microbes belowground. We also observed increased association of beneficial bacterium Bacillus subtilis UD1022 on roots of the neighboring plants sharing environment with the damaged plants. Wounding-induced plant-derived signals therefore induce defense mechanisms in the undamaged, local plants, eliciting a two-pronged preemptive response of more rapid root growth and up-regulation of ALMT1, resulting in increased association with beneficial microbiome.